Another one that extends the toe: the Austregésilo-Esposel sign Uno más que extiende el primer ortejo: el signo de Austregésilo-Esposel - Castillo Flores, Sergio Andrés; Flores Alfaro, Fernanda; Góngora Rivera, Juan Fernando (Academia Brasileira de Neurologia, 2021)
With great interest we read the article by Novis and colleagues recently published in Arquivos de Neuro-Psiquiatria1. Where they present the life and work of Professor Faustino Esposel, considered the father of Brazilian neurology, who along with Antõnio Austregésilo, described a substitute sign for Babinski’s phenomenon eliciting of the extensor plantar response upon squeezing of the thigh: “Le phénomene de Babinski, provoqué par l’excitation de la cuisse”, now known as the Austregésilo-Esposel sign2. Upon a search of the literature, we were unable to find recent visual documentation of the sign. Therefore, to illustrate the excellent article by Novis and colleagues, we considered it appropriate to present the case of a patient with stroke in whom the Austregésilo-Esposel sign was present, along with the Babinski, Chaddock, and Oppenheim signs.